Honest Signaling and Oxidative Stress: The Special Case of Avian Acoustic Communication - Casagrande, Stefania; Pinxten, Rianne; Eens, Marcel (Frontiers in Ecology and Evolution, 2016)
Much research on animal communication has addressed how costs or constraints determined by the oxidative status of an individual can assure the honesty of visual signals, such as sexually selected color ornaments. However, acoustic communication has been largely overlooked in this respect. Here, we describe the few available studies that have considered the role of oxidative status in mediating vocal behavior in adult and nestling birds. Further, we discuss the theoretical principles of how the honesty of avian acoustic signals may be maintained by an organism’s oxidative status. We here distinguish between studies that considered songs and begging calls as indicators of oxidative status and studies where vocalizations were assumed to be the source of oxidative costs. We outline experimental and methodological issues related to the study of bird vocalizations and oxidative stress and describe opportunities for future work in this field of research. Investigating the interactions between acoustic signals and redox state may help address some unresolved questions in avian vocalization, thereby increasing our understanding of the evolutionary pressures shaping animal communication. Finally, we argue that it will be important to extend this line of research beyond birds and include other taxa as well.